2021
DOI: 10.1186/s41043-021-00250-1
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional quality of beverages available in vending machines in health and social care institutions: do we really want such offers?

Abstract: Background Vending machines represent one way of offering food, but they are overlooked in the efforts to improve people’s eating habits. The aim of our study was to analyse the variety and nutritional values of beverages offered in vending machines in social and health care institution in Slovenia. Methods The available beverages were quantitatively assessed using traffic light profiling and the model for nutrient profiling used by Food Standards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 42 publications
(12 reference statements)
0
5
0
3
Order By: Relevance
“…This parallels the result of Brown et al ( 18 ) , although their reported increase (50 %) was much larger. These findings suggests that in settings where mostly unhealthy items are on offer (such as vending machines ( 14 16 ) ), using traffic lights alone may not be enough to produce a substantial shift towards healthier choices. Traffic lights have been shown to be successful in increasing healthy choices in settings that typically offer a greater variety of healthy items (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This parallels the result of Brown et al ( 18 ) , although their reported increase (50 %) was much larger. These findings suggests that in settings where mostly unhealthy items are on offer (such as vending machines ( 14 16 ) ), using traffic lights alone may not be enough to produce a substantial shift towards healthier choices. Traffic lights have been shown to be successful in increasing healthy choices in settings that typically offer a greater variety of healthy items (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…One environment that is a common source of soft drinks is a vending machine, which often feature a disproportionately high number of sugar-sweetened beverages (14)(15)(16) . Additionally, vending machines do not typically offer nutritional information at the point of purchase.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… List only include studies where Slovenian branded food databases were exploited directly. Food monitoring studies datasets were used for several other studies, for example, to support in the sampling of foods in the food supply for assessment of the content of trans fatty acids in foods ( 64 , 65 ), for assessment of salt iodization ( 66 ), for assessment of dietary intakes ( 67 71 ), food marketing ( 25 , 72 74 ) and offers in vending machines ( 75 , 76 ). Studies exploiting additional Slovenian branded foods composition datasets ( 44 , 66 , 77 79 ) are also not included .…”
Section: The Exploitation Of Use Of Branded Foods Database In Nutrition Researchmentioning
confidence: 99%
“…Similarly, the nutritional quality of foods available in vending machines was also investigated. Rozman et al reported the poor nutritional quality of snacks ( 75 ) and beverages ( 76 ) available in vending machines in health and social care institutions in Slovenia.…”
Section: The Exploitation Of Use Of Branded Foods Database In Nutrition Researchmentioning
confidence: 99%